Toba na sae : sejarah ringkas lahirnya institusi-institusi organisasi parbaringin dan dinasti Singamangaraja dalam sejarah suku bangsa Batak-Toba - Situmorang, Sitor, 1923- (Jakarta : Pustaka Sinar Harapan, 1993)
History of socio-culture of Toba Batak, an ethnic group of North Sumatra.
Keywords: Sisingamangaraja -- XII, -- Raja, -- approximately 1860-1907.; Batak (Indonesian people) -- History; Batak (Indonesian people) -- Politics and government; Sumatera Utara (Indonesia) -- Politics and government